Folklore Functions and Noble Values in The Performance of Wayang Gagrak Porongan - Habibah Rizka Nur Annisa'; Maulfi Syaiful Rizal (Sutasoma : Jurnal Sastra Jawa, 2026)
Wayang Gagrak Porongan has experienced a period of decline due to limited performance spaces and a lack of generational succession among artists. Therefore, this study aims to document, preserve, and reveal the noble cultural identity embodied in Wayang Gagrak Porongan performances. This study use descriptive qualitative method. Data were collected through observation, interviews, performance documentation, and a synopsis of the story, Wahyu Catur Pujangga. The data were analyzed using William R. Bascom’s theory of folklore functions. The analysis involved selecting relevant data, presenting the findings in descriptive narratives and classification tables, and drawing conclusions verified through methodological triangulation. Research result: first, the projection function is reflected in societal expectations regarding the ability to lead oneself and in the projection of the community’s straightforward character. Second, the function of validating cultural institutions is manifested through the recognition of the Gagrak Porongan identity and the Taruna Budaya institution's involvement in organizing the performance. Third, the educational function is conveyed through the advice of the Punakawan characters, which promotes humility and mutual respect. Furthermore, the noble values identified include religious values, reflected in spiritual practices before and during the performance, and moral values, embodied in Cangkruk's culture as a medium for strengthening solidarity and kinship within the community.